Novel insight on temporary frequency support of variable speed wind energy conversion system - Huanjing Lao; Li Zhang; Tong Zhao; Liang Zou (Wind Energy, 2021)
Abstract In the recent decade, temporary frequency support derived from variable speed wind turbine generator has been drawing increasing attention in the electronic‐growing power system. Frequency nadir and rate of change of frequency are two key indicators temporary frequency support strives to improve. This paper proposes a novel insight on frequency regulation of wind power. Note that considerable part of load is shared by synchronous generators and wind turbine generator and the system frequency still will be dominated by the former for a period of time. Simultaneously taking the frequency regulation characteristic of synchronous and power balance into account, a novel frequency regulation scheme aiming at improving system's frequency regulation performance is proposed and tested in a 7‐machine power system with an aggregated wind farm on MATLAB/Simulink to investigate what inherently determines the performance of frequency regulation. Results show that with differential cooperation of synchronous generator and doubly fed induction generator, frequency nadir and rate of change of frequency can be partially improved. Particularly, regarding to handling the issue of control delay, an appropriately slower action upon detecting a frequency event may not screw up it but contribute to a higher frequency nadir, which benefits from the spontaneous cooperation of synchronous generator and wind power with constraint of power balance.